Proteomics and Phosphoproteomics of Heat Stress-Responsive Mechanisms in Spinach - Zhao, Qi; Chen, Wenxin; Bian, Jiayi; Xie, Hao; Li, Ying; Xu, Chenxi; Ma, Jun; Guo, Siyi; Chen, Jiaying; Cai, Xiaofeng; Wang, Xiaoli; Wang, Quanhua; et al. (Frontiers in Plant Science, 2018)
Elevated temperature limits plant growth and reproduction and poses a growing threat to agriculture. Plant heat stress response is highly conserved and fine-tuned in multiple pathways. Spinach (Spinacia oleracea L.) is a cold tolerant but heat sensitive green leafy vegetable. In this study, heat adaptation mechanisms in spinach sibling inbred heat-tolerant line Sp75 were investigated using physiology, proteomics, and phosphoproteomics approaches. The abundance patterns of 911 heat stress-responsive proteins, and phosphorylation level changes of 45 phosphoproteins indicated that heat induced calcium-mediated signaling, ROS homeostasis, endomembrane trafficking, and cross-membrane transport pathways, as well as > 15 transcription regulation factors. Although photosynthesis was inhibited, diverse primary and secondary metabolisms were employed for enhancing thermotolerance, such as glycolysis, pentose phosphate pathway, amino acid metabolism, fatty acid metabolism, nucleotide metabolism, vitamin metabolism, and isoprenoid biosynthesis. These data constitutes a heat stress-responsive metabolic atlas in spinach, which will springboard further investigation into the sophisticated molecular mechanism of plant heat adaptation and inform spinach molecular breeding initiatives.